1965
DOI: 10.2135/cropsci1965.0011183x000500060018x
|View full text |Cite
|
Sign up to set email alerts
|

Heterosis and Combining Ability in Upland Cotton—Effect on Yield1

Abstract: I festation of heterosis k n o w n as h y b r i d vigor, has received increased attention from cotton breeders. Heterosis was first utilized in obtaining increased production in asexually propagated plants. Through the use of malesterility, gametocides, and imperfect-flowered plants, heterosis is now used to advantage in many species. Considerable evidence exists (4) t h a t heterosis is expressed in crosses between Gossypz'um hiisutum (Upland cotton) and G. barb~rdeizse (e x t r a-l o n g staple cotton). Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

1971
1971
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 0 publications
1
4
0
1
Order By: Relevance
“…Results are in agreement with those of Marani (1963); Hawkins et al (1965), Young and Murray (1966) and Rafique (1972).…”
Section: Seed Cotton Yield In Relation To Mature Bolls and Plant Popusupporting
confidence: 92%
“…Results are in agreement with those of Marani (1963); Hawkins et al (1965), Young and Murray (1966) and Rafique (1972).…”
Section: Seed Cotton Yield In Relation To Mature Bolls and Plant Popusupporting
confidence: 92%
“…Degree of heterosis and relatedness were not correlated (Tables 2 and 5). Hawkins et al (1965) also found increasing heterosis associated with decreasing environmental mean. They attributed this to similar hybrid response over all environments where the relative percent heterosis declined as inbred means increased.…”
Section: Heterosismentioning
confidence: 78%
“…They attributed this to similar hybrid response over all environments where the relative percent heterosis declined as inbred means increased. Hawkins et al (1965) also found increasing heterosis associated with decreasing environmental mean. Heterotic response, however, was not consistent across environments, resulting in 35.0, 16.6, and 9.2% high-parent heterosis for environments that had means of 642, 712, and 1005 kg lint ha -1 , respectively.…”
Section: Heterosismentioning
confidence: 78%
“…Valores heteróticos variando de 18% a 35% foram obtidos por Miller & Lee (1964). Hawkins et al (1965) encontraram valor heterótico de 24% e vários de seus híbridos foram significativamente mais produtivos do que o melhor progenitor. Os valores heteróticos registrados nesses trabalhos foram de alta magnitude, principalmente quanto às características produção, número de capulhos e tamanho do capulho.…”
Section: Introductionunclassified